Impact of Intrinsic Motivation and Transformation Leadership on Employees Productive Behavior of Manufacture Company in Sidoarjo, Indonesia - Rizki Eko Wibowo; Rifdah Abadiyah (Universitas Muhammadiyah Sidoarjo, 2019)
This study aims to determine the effect of Self Efficacy, Intrinsic Motivation, Employee Engagement, and Transformational Leadership on the Productive Behavior of Employees at PT. Korin Intiwira Sejahtera Sidoarjo. The analytical tool used is to tabulate the data coellection questionnaireiin the form of a validity reliability test, the hiypothes is in this study is Self Efficacy, Intrinsic Motivation, Employee Engagement, and Transformational Leadership Productive Behavior of Employees. The research a results obtained based on the validity test showed that all statements on the questionnaire were declared valid. For the reliability test of all variables, the Crombach Alpha value >0.6 was declared valid. And for hypothesis testing based on the F test, the t test and adjusted R2 show that there is a significant influence between Self Efficacy, Intrinsic Motivation, Employee Engagement, and Transformational Leadership on Productive Behavior of Employees.